Assessing user preferences and competitive strategies of Gojek and Grab in ASEAN’s ride-hailing market - Pandu Kurniawan; Didi Achjari (Innovative Marketing)
Along with the development of current economic patterns, digital platforms provide infrastructure to facilitate interaction between users. One example is a ride-hailing platform that allows interaction between users who may never have met. This study aims to determine the criteria, sub-criteria, and alternatives influencing users in choosing ride-hailing and map Gojek and Grab’s grand strategy to compete in the ASEAN market, especially in Indonesia, Thailand, Vietnam, and Singapore. This research uses a questionnaire to collect data, with 377 Gojek and Grab users as participants. The main criteria in each country were obtained using the Analytical Hierarchy Process (AHP) method with the Expert Choice tool. Safety, price, and usability were the main criteria for choosing a ride-hailing platform in Indonesia, Thailand, and Vietnam. In contrast, in Singapore, privacy emerged as the main criterion when choosing these platforms, in addition to safety. To increase competition in ASEAN, Gojek and Grab should improve customer relationship criteria, as these criteria can add value to the company. This research also shows that Grab dominates the ride-hailing market in Thailand, Vietnam, and Singapore because it implemented a horizontal strategy by acquiring Uber. Gojek only excels in its home country, Indonesia, by acquiring and innovating in integrating with the commuter line and launching an Initial Public Offering (IPO). This research found that there is still a need to improve vertical and horizontal strategies and outsourcing to compete effectively in the global market.